Transcriptome profiling the basal region of poplar stems during the early gravitropic response - W. Azri; A. Ennajah; Z. Nasr; S. -Y. Woo; A. Khaldi (Biologia Plantarum, 2014)
Stems of angiosperm trees are affected by gravity. Young poplar stems show primary growth in the top internodes and differential cambium activity in the basal internodes after inclination with some tension wood formed after 45 min. This study was conducted in order to characterize the early changes in poplar gene expression during the early stages of the gravitropic response. Using microarray technology, the expression of 15 000 genes was examined. Approximately 3.1 % of these genes exhibited significant expression changes within the first 45 min of gravity stimulation. Approximately 73 % of the identified genes were found to have a known or predicted molecular function. Many of these genes were involved in secondary wall formation (cellulose synthesis and lignification), cytoskeleton development, signaling, and stress response. Some identified genes seem to play a role in sensing gravitational signals during tension wood formation. A large number of the identified arabinogalactan (AGP) and transcription factor genes were involved in cell wall biosynthesis suggesting that these genes are particularly active in the first phases of signal transduction during tension wood formation.